Penerapan Sikap Disiplin Melalui Pembiasaan Shalat Dhuha Pada Anak Usia Dini Di TK Assalam - Harmini - Harmini (JIEEC (Journal of Islamic Education for Early Childhood), 2022)
To find out how to plan the implementation of dhuha prayer through habituation of dhuha prayer in early childhood in Assalam Kindergarten and know the process of applying discipline through habituation of dhuha prayer in early childhood in Assalam Kindergarten and to know the supporting and inhibiting factors of implementing discipline through habituation of dhuha prayer in early childhood in Assalam Kindergarten. This study uses a qualitative approach with descriptive research type to describe the empirical reality behind the phenomena that occur in Assalam Kindergarten in the application of discipline through habituation of dhuha prayer by explaining a phenomenon that occurs in Assalam Kindergarten as deeply as possible. Based on the results of the initial research obtained from observations in Assalam Kindergarten, that planning for the application of child discipline through habituation of dhuha prayer develops in accordance with expectations. It can be seen from the children who are still running around when the habituation is carried out, there are still children who are cool in their own world, there are children who are still screaming and do not focus on the activities being carried out. Assalam Kindergarten in the application of discipline by habituation of sunnah prayers, the teacher being a good example through continuous guidance and assistance can help instill a disciplined, obedient and orderly attitude to the rules, can help instill commendable morals from an early age and can introduce teachings Islamic teachings from an early age. The role of teachers in schools as role models and good examples greatly influences the smoothness and success of the learning programs carried out, as well as the important role of parents who help guide students at home.